Photocatalytic Oxidation of α‐C−H Bonds in Unsaturated Hydrocarbons through a Radical Pathway Induced by a Molecular Cocatalyst. Issue 12 (6th June 2019) - Zhao, Guixia; Hu, Bin; Busser, G. Wilma; Peng, Baoxiang; Muhler, Martin
Abstract: To improve the photocatalytic oxidation of α‐C−H bonds in unsaturated hydrocarbons, N ‐hydroxyphthalimide (NHPI) was used as a molecular cocatalyst with CdS as the photoabsorber. Compared with previously reported photocatalysts involving solid cocatalysts, metal‐free NHPI offers better sustainability in addition to the significantly enhanced performance as cocatalyst. The photogenerated holes were transferred into the more active phthalimide‐ N ‐oxyl radical (PINO) by reacting with NHPI. In this way, α‐C−H bond oxidation was significantly improved through the activation by PINO; even for the sluggish toluene oxidation, the apparent quantum efficiency was as high as 36.5 %. The effects of substrates/NHPI concentration ratio, reaction temperature, and time as well as the reaction intermediates were comprehensively studied. It was possible to identify ketones/aldehydes as the primary products, and overoxidation was controlled by adjusting the substrates/NHPI concentration ratio and reaction time. Thus, the radical path induced by the NHPI–PINO redox pair is an efficient alternative to boost the sluggish photocatalytic oxidation of α‐C−H bonds. Abstract : C−H activation : Toluene oxidation is triggered indirectly with enhanced efficiency by the radical intermediate phthalimide‐ N ‐oxyl (PINO), which originates from N ‐hydroxyphthalimide (NHPI) oxidation by photogenerated holes in CdS. The NHPI–PINO redox pair offers a sustainable cocatalyst alternative to boost the photocatalytic oxidation of α‐C−H bonds.